2003
DOI: 10.1038/sj.bjc.6600779
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein regulates the effects of amifostine on apoptosis, cell cycle progression, and cytoprotection

Abstract: To determine the role of p53 protein on the cellular effects of amifostine, we used molecularly engineered HCT116 colon cancer cells in which the p53 gene was inactivated by targeted homologous recombination or p53 protein was degraded by high-level expression of papillomavirus E6 protein. Amifostine induced a G1 arrest and protected against paclitaxel toxicity in p53-proficient but not in p53-deficient cells. In the absence of p53 protein, amifostine enhanced the cytotoxicity of paclitaxel. In addition, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…The effect of WR1065 on apoptosis is minimal, as demonstrated by the absence of any significant subdiploid population of cells (Figure 4), the absence of morphologically detectable cell death, and the lack of caspase-mediated PARP degradation (Figure 3). Our results contrast with the results of Lee EJ et al (2003) in which amifostine increases apoptosis in p53-negative HCT116 cells, whereas the presence of p53 protein actually confers resistance to this amifostine-induced apoptosis. However, the high concentration (3.8 mM) of amifostine used in the study of Lee et al could, on conversion of the prodrug to the aminothiol, result in a concentration of WR1065 greater than the 1.5 mM dosage, which we have shown to be cytotoxic.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The effect of WR1065 on apoptosis is minimal, as demonstrated by the absence of any significant subdiploid population of cells (Figure 4), the absence of morphologically detectable cell death, and the lack of caspase-mediated PARP degradation (Figure 3). Our results contrast with the results of Lee EJ et al (2003) in which amifostine increases apoptosis in p53-negative HCT116 cells, whereas the presence of p53 protein actually confers resistance to this amifostine-induced apoptosis. However, the high concentration (3.8 mM) of amifostine used in the study of Lee et al could, on conversion of the prodrug to the aminothiol, result in a concentration of WR1065 greater than the 1.5 mM dosage, which we have shown to be cytotoxic.…”
Section: Discussioncontrasting
confidence: 56%
“…In a number of experimental systems, WR1065 exerts antimutagenic and cytoprotective effects at concentrations ranging between 100 mM and 1 mM and can even induce p53 accumulation at concentrations as low as 50 mM (North et al, 2000). Also, the absence of AG in the culture medium in the experiments by Lee EJ et al (2003) may result in the generation of toxic products from amifostine breakdown. Previously, transcription of several genes has been reported to be altered by treatment with WR1065: p21 is upregulated by treatment of cells containing wild-type p53 (North et al, 2000), as are fas, gadd45, and mdm2 (Shen et al, 2001), whereas MnSOD is upregulated in response to WR1065 activation of NF-kB (Kataoka et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer cells amifostine caused p53-proficient cells to arrest in G1 and provided protection against the cytotoxic effects of paclitaxel, but these effects of amifostine were not seen in p53-deficient cells. 22 However, yet another study investigated amifostine's cytoprotection of human glioma cells during radiation therapy and found that it was independent of p53 status. 23 We suggest that amifostine-mediated cell death may result from two different mechanisms.…”
Section: Induction Of Apoptosis In Human Lung Cancer Cells a Pataer Ementioning
confidence: 99%
“…Amifostine induced a G 1 arrest and protected against paclitaxel toxicity in cells with functional p53 (32). In contrast, amifostine enhanced the cytotoxicity of paclitaxel in the absence of p53.…”
Section: Discussionmentioning
confidence: 94%